Implementation Of A Portfolio-Based Learning Model To Improve Mathematics Learning Outcomes Of Primary School Students: Indonesia - Farida (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2020)
This study aims to see the activities and learning outcomes of students by applying a portfolio-based learning model. This type of research is classroom action research or Classroom Action Research. This research was applied to class VI SD Negeri 23 Ampalu, Ranah Pesisir District. Activities in research are planned in the form of cycles and each cycle consists of planning, implementation, observation, and reflection. The tools for collecting research data are planned in the form of, 1) Observation format to see aspects that can be observed in the learning process at every meeting, 2) Portfolio assessment format to include the value of the entire series of student activities during the learning process. The data analysis technique is carried out with the first two activities, the analysis of the results of the observations is carried out by determining the percentage of student activity in each aspect that is observed, the second is the analysis of the entire series of student activities that have been assessed at the end of the learning process by looking for the average of each meeting so that the research can look for data on the level of student learning activeness. and the improvement after action 1, then the researcher made the necessary corrective steps for the next action. The results showed that the portfolio assessment in the first and second cycles with an average value of 73.58 and 79.00, so based on the results of this study it can be concluded that learning with portfolio assessment can improve student activity and learning outcomes.